The effect of carbohydrate gel consumption on elite mountain bikers time to exhaustion and blood glucose metabolism
Study Objectives: In athletes, additional carbohydrate (CHO) uptake is important during submaximal and high-intensity exercise and competitions where the cost of metabolism exceeds endogenous carbohydrate depots. The aim of this study was to investigate the effects of carbohydrate gel consumption on glucose concentration and exercise time to exhaustion of elite mountain bikers. Methods: 20 mountain bikers (22,5 Å